Emery and Rimoin's principles and practice of medical genetics and genomics. - Pyeritz, Reed E.; Korf, Bruce R.; Grody, Wayne W. (Academic Press is an imprint of Elsevier, 2019)
"The Seventh Edition of this classic reference includes the latest information on seminal topics such as prenatal diagnosis, genome and exome sequencing, public health genetics, genetic counseling, and management and treatment strategies to complete its coverage of this growing field for medical students, residents, physicians, and researchers involved in the care of patients with genetic conditions. This comprehensive yet practical resource emphasizes theory and research fundamentals related to applications of medical genetics across the full spectrum of inherited disorders and applications to medicine more broadly. Clinical Principles and Applications thoroughly addresses general methods and approaches to genetic counseling, genetic diagnostics, treatment pathways, and drug discovery. Additionally, new and updated chapters explore the clinical implementation of genomic technologies, analytics, and therapeutics, with special attention paid to developing technologies, common challenges, patient care, and ethical and legal aspects. With regular advances in genomic technologies propelling precision medicine into the clinic, the seventh edition of Emery and Rimoin's Principles and Practice of Medical Genetics and Genomics bridges the gap between high-level molecular genetics and practical application"--Publisher's description